Learning meaningful latent space representations for patient risk stratification: model development and validation for dengue and other acute febrile illnes - Hernandez, B; Stiff, O; Ming, DK; Ho Quang, C; Nguyen Lam, V; Nguyen Minh, T; Nguyen Van Vinh, C; Nguyen Minh, N; Nguyen Quang, H; Phung Khanh, L; Dong Thi Hoai, T; Dinh The, T; et al. (Frontiers Media, 2023)
Background: Increased data availability has prompted the creation of clinical decision support systems. These systems utilise clinical information to enhance health care provision, both to predict the likelihood of specific clinical outcomes or evaluate the risk of further complications. However, their adoption remains low due to concerns regarding the quality of recommendations, and a lack of clarity on how results are best obtained and presented.